Urban agriculture and policy: mitigating urban negative externalities - V. D., Nirusha Ayoni; Ramli, Nurul Nadia; Shamsudin, Mad Nasir; Abdul Hadi, Ahmad Hanis Izani (Elsevier, 2022)
Agriculture and urban agglomerations can be combined in different perspectives, including building-integrated food production. Indeed, urban agriculture is less concerned with helping urban communities achieve food self-sufficiency and more concerned with strengthening urban inhabitants differently. "Different" signifies multifunctional forms of access to fresh and nutritious vegetables, food bill reduction, personal well-being, and user-friendly agriculture from socioeconomic perspectives. The study estimated willingness to pay and the value of socioeconomic benefits of urban agriculture practices. A choice experiment was performed in Colombo, Sri Lanka's most urbanized district in 2020. The data were estimated using the random parameter logit model. Positive and significant contributions to urban agriculture related to the utility of urban agriculture practitioners and non-practitioners were evident. The socioeconomic value of urban agriculture benefits generated is equivalent to USD 136,400 per community practices urban agriculture. Urban agriculture thus reveals its vitality as a tool for mitigating the negative impacts of urbanization. The research advocates Colombo municipality to actively encourage urban agriculture by including it in their planning policies.